Nurses' Moral Problems in Dialisys - Hermsen, Maaike (Nursing ethics, 2009)
This article gives an overview of the moral problems experienced and described by nurses working in a dialysis unit in the Netherlands. The nurses raised a wide variety of issues that they considered were moral problems, which were grouped into seven topics. A selection of cases are described, one of which is analysed using the Nijmegen method of ethical case deliberation. This method facilitates practical approaches to the different types of moral problems encountered. The argument is made that, owing to their specific moral position and responsibility, nurses' contribution to ethical reflection in ward discussions should be valued more. All caregivers involved are indispensable in developing a basis for well-reasoned decisions when deliberating about moral problems.